Concrete buildings in seismic regions - Penelis, George G.; Penelis, Gregory G. (New York : CRC Press, 2014)
'This practical book presents current approaches to seismic analysis and design, with a particular focus on reinforced concrete structures. It covers the earthquake resistant design of new buildings, and the assessment, repair and retrofit-strengthening of existing buildings. It also covers the post-earthquake damage assessment and evaluation of existing buildings and outlines the seismic risk mitigation procedures for urban regions. The book is for practicing engineers and graduate students'--
'Preface This book is addressed primarily to postgraduate students in earthquake engineering and to practicing structural engineers specialising in the design of R/C seismic-resistant buildings. The basic aims that have guided the composition of the material of this book are the following: 1. The presentation of the content should be characterised by integrity, clarity and simplicity, particularly for the design procedure of new R/C buildings or assessment and retrofitting of existing ones. In this respect it would constitute integrated knowledge for a student. We hope that the long experience of the first of the authors in teaching undergraduate and postgraduate students about R/C earthquake-resistant structures augurs well for the achievement of this aim. 2. The presentation of the scientific background of each subject should be made in a concise form with all the necessary--but at the same time, limited--references to the sources so that enough of an open field is available for a rigorous and systematic approach to the implementation of the scientific background in design procedure. In this context, this book would be valuable for a practicing engineer who wants to have in-depth knowledge of the background on which the Code rules are based. We hope that the extensive experience of both authors in the seismic design of new R/C buildings and in the assessment and retrofitting of existing ones, together with the wide experience of the first in posts of responsibility in seismic risk management in Greece, contribute to a balanced merging of the scientific background with practical design issues. At the same time, the numerical examples that are interspersed in the various chapters also intend to serve this aim'--
Includes bibliographical references and index.
Keywords: Reinforced concrete construction; Buildings, Reinforced concrete -- Earthquake effects; Earthquake resistant design